SCN1A and Susceptibility to MTL Epilepsy, Hippocampal Sclerosis and Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs, 2013)
Investigators at the Department of Clinical and Experimental Epilepsy, Institute of Neurology, Queen Square, London, and other centers in the UK and Europe conducted a genome-wide association study in 1018 people with mesial temporal lobe epilepsy (MTLE) with hippocampal sclerosis and 7552 control subjects, with (n=757) and without (n=803) a history of febrile seizures.